Pengembangan Strategi Dan 1ntervensi Komunikasi Informasi Edukasi-Keluarga Berencana (Kie-Kb) Daerah Aliran Sungai (Das) Di Kalimantan Selatan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT This study was based on the data which showed that the family planning participants in the area along the river (DAS) in South Borneo was still poor and was below the average of the provincial target. This study was an attempt at scrutinizing the data of participants of family planning DAS, especially participants, non-participants, participants of UPPK, participants of BKB, participants of non-BKB, local market community living in a potential local market. There is a follow up on the strategy model on needs and influence of Education Information Communication-Family Planning (K1E-KB) such as mass media, messages, figure, and requirednes of K!E. The condition of DAS in East Borneo is relatively similar, either its location or the number, of participants of family planning. Three residences were chosen as the research areas, i.e. residence of Banjar, Hulu Sungai Utara and Barito Kuala. In each residence, three sub-districts were chosen and in each sub-district, four villages were chosen. The subject of the research were 450 respondents. The data analysis was conducted descriptively, qualitatively and quantitatively. It was found out that there were differences on knowledge, perception and family planning practice on the segments of family planning participants, non-participants, participants of UPPK, participants of BKB, participants of non-BKB, local market environment and community living in the potential local market.